Behavior of 137Cs in the soil-plant system in the floodplain landscapes of the Sozh River basin - A. L. Silaev; E. V. Smolsky; L. D. Skovikova (Бюллетень Почвенного института им. В.В. Докучаева, 2024)
Studies were carried out in the most affected by the Chernobyl accident part of the Bryansk region, in the ecosystems of floodplains of the Iput, Besed and Unecha rivers, in zones with different 137Cs pollution density. The purpose of the work is to study the peculiarities of the vertical distribution of 137Cs in the soil–plant system of the floodplain landscape long after the Chernobyl accident. As a result of studies, it was revealed that the vertical distribution of 137Cs, in the 0–20 cm layer, is determined by the position on the relief and the genesis of the soils of floodplain subsystems. The distribution character can be uniform, decreasing with depth, or with accumulation in certain layers. In the floodplain ecosystem, the concentration of 137Cs in the 0–20 cm layer increases from the river channel to the terrace above floodplain subsystems. Currently, the use of the territory of the west of the Bryansk region with a 137Cs pollution density above 555 kBq/m2 in feed production is strictly limited. The coefficient of 137Cs transition from soil to plants decreases from the central part to the near-channel one and to terrace above floodplain.